Quantum Brownian motion induced by a scalar field in Einstein’s universe under Dirichlet and Neumann boundary conditions - E. J. B. Ferreira; H. F. Santana Mota (European Physical Journal C: Particles and Fields)
Abstract In this paper, the quantum Brownian motion of a point particle induced by the quantum vacuum fluctuations of a real massless scalar field in Einstein’s universe under Dirichlet and Neumann boundary conditions is studied. Using the Wightman functions, general expressions for the renormalized dispersion of the physical momentum are derived. Distinct expressions are found for the dispersion associated with each component of the particle’s physical momentum, indicating that the global properties of homogeneity and isotropy of space are lost, as a consequence of the introduced boundary conditions. Divergences also arise and are related to the compact nature of Einstein’s universe and the introduced boundary conditions.